Efficacy Of Combined Decontamination and Neuroprotection in the Treatment of Sepsis in Infants During the First Year of Life (Eurasian Medical Research Periodical, 2022)
The article presents the results of a study on the effectiveness of sepsis treatment using combined decontamination and enterosuction in young children.